Formation Kinetics and Antimicrobial Activity of Silver Nanoparticle Dispersions Based on N-Reacetylated Oligochitosan Solutions for Biomedical Applications - Ekaterina K. Urodkova; Ol'ga Ya. Uryupina; Vladimir E. Tikhonov; Natalia E. Grammatikova; Anastasia V. Bol'shakova; Anna A. Sinelshchikova; Alexandra I. Zvyagina; Dmitry N. Khmelenin; Elena S. Zhavoronok; Ivan N. Senchikhin (MDPI AG, 2023)
The paper presents the results of the synthesis, a detailed kinetics study, and an investigation of the biological activity of silver nanoparticles (AgNPs) in aqueous solutions of N-reacetylated oligochitosan hydrochloride. UV-visible spectrophotometry and dynamic light scattering were employed to control silver ion reduction. The process was observed to follow a pseudo-first-order law. Transmission and scanning electron microscopy demonstrated that AgNPs ranging in size from 10 to 25 nm formed aggregates measuring 60 to 90 nm, with the aggregate surface coated by a 2-4 nm chitosan shell. X-ray microanalysis and powder X-ray diffractometry were used to study the phase composition, identifying two crystalline phases, nanocrystalline silver and AgCl, present in the dispersions. The antibacterial effect was assessed using the serial dilution method for dispersions with varying degrees of Ag+ conversion. Nanodispersions exhibited significant activity against Escherichia coli, Pseudomonas aeruginosa, Bacillus cereus, and Staphylococcus aureus. Interestingly, the activity did not appear to be heavily influenced by the presence of the AgCl phase or the concentration of Ag+ ions. These synthesized dispersions hold promise for the development of materials tailored for biomedical applications.